Development of Oral Health Promotion Model of School Children with Participation of Network Partners in Lamlukka Municipality, Pathumthani Province - Suttagul, Kanokwan (NU Journal of Nursing and Health Sciences, 2022)
According to The 2017 National Oral Health Survey of 12 year old found 52.0% of the prevalence of tooth caries and gingivitis increased. This research and development aimed to develop oral health promotion competency of school age children with participation of network partners and to study the effect of the oral health promotion activity programe in 85 students, 6 teachers, 2 public health officers, and 4 registered nurses. Duration of the study was run from March - May 2021 using questionnaires with oral health status records. The content validity of instruments were 0.87 and the reliability of the questionnaire was 0.851. Research methodology including 1) problem diagnosis 2) the period of development of the model and applying to use, and 3) evaluation period. Statistical analysis was done using descriptive statistics, pair t-tests, and content analysis. Results: students had low to moderate knowledge, attitude, and practice on oral health. The Learn Fun & 3C oral health promotion model was developed for students in 2 activities with 3 times. The overall mean scores on knowledge, attitude, and practice after participating the program were higher than before (x̄=4.6, S.D.=1.46, x̄=2.6, S.D.=0.97 and x̄ =3.8, S.D.=1.12) at significance level (p<0.01) and had lower gingivitis and plaque score than before participating in the activity. Therefore, educational activities should organize to promote oral health among students continuously.